Molecular epidemiology and phylogenetics of camel anaplasmosis - Farhan Ahmad Atif; Ammar Tahir; Muhammad Kashif; Aziz ur Rehman; Abdulmohsen H. Alqhtani; Alaa Bassuny Ismael; Ioannis A. Giantsis; Adil Khan; Furhan Iqbal; Muhammad Imran; Ayman A. Swelum (PLoS ONE, 2025)
Camel anaplasmosis is a tick-borne disease of zoonotic concern, yet its epidemiology in Pakistan remains understudied. This study aimed to determine the prevalence, associated risk factors, and phylogenetic characteristics of Anaplasma spp. in camels across diverse agro-climatic zones of Punjab. A total of 400 blood samples were collected from two districts—Jhang and Bahawalpur (n = 200 each)—using a multistage cluster sampling approach. From each district, four tehsils were selected; ten herds per tehsil were sampled, with five camels per herd. The PCR targeting the 16S rRNA gene was used for Anaplasma detection. Epidemiological data were gathered using a structured questionnaire. The overall prevalence was 25.75%. Multivariable analysis identified age (>5 years), district (Jhang), intensive management, and health status as significant risk factors. Phylogenetic analysis revealed that A. phagocytophilum isolates were genetically related to strains from India, Iran, and Turkey; A. platys showed proximity to dog-derived isolates from India, South Africa, and Spain; while Candidatus A. camelii was closely related to camel isolates from Egypt, China, Kenya, and Iran. In conclusion, camel anaplasmosis is prevalent in Punjab. Further research is warranted to explore the pathogenic potential and vector dynamics of circulating strains to devise control strategies.